Ecology of litterfall production of giant bamboo Dendrocalamus asper in a watershed area - A.G. Toledo Bruno; R.A. Marin; M.A.P. Medina; G.R. Puno; R.O. Villarta; R.R. Puno (Global Journal of Environmental Science and Management)
Giant bamboo Dendrocalamus asper is recommended in environmental and livelihood programs in the Philippines due to its various ecological, economic and social benefits. However, there are limited data on the ecology of giant bamboo litterfall production, which contributes to soil nutrient availability. Bamboo also contributed in carbon sequestration. The study was conducted within the Taganibong Watershed in Bukidnon, Philippines. Nine litterfall traps measuring 1mx1m were established within the giant bamboo stand in the study area. Results show that giant bamboo litterfall is dominated by leaves. Biological characteristics of bamboo litterfall do no not influence litterfall production but temperature, wind speed and humidity correlate with the amount of litterfall. Findings of the study further revealed that fresh giant bamboo tissue contains high carbon content and the soil in the bamboo stand has higher organic matter than the open clearing. These data indicate the role of giant bamboo in carbon sequestration and soil nutrient availability.